A Rapid Procedure for the Approximation of Bacterial Load in Fishery Products - Mathen, Cyriac; Lekshmy, A; Iyer, H Krishna; Pillai, V K (Fishery Technology, 1964)
The production of colour by homogenised fish material in a simplified sugar medium containing an acid indicator has been made use of for the rapid approximation of bacterial load in such products. The medium thus developed contains peptone, tryptone, yeast extract, sodium chloride andbeef extract besides dextrose. The time of colour production is influenced to some extent by the level of sodium chloride in the medium: and is almost always inversely proportional to the bacterial load in the homogenate.